2020
DOI: 10.1021/acssuschemeng.0c06122
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Effects between Oxygen Groups and Defects in Hydrodeoxygenation of Biomass over a Carbon Nanosphere Supported Pd Catalyst

Abstract: This work reports an innovative route for biomass upgrading via hydrodeoxygenation (HDO) reactions which avoids external high-pressure hydrogen supply and harsh conditions (such as high-temperature or additives). A novel Pd/CFR catalyst with controllable oxygen groups and defects was synthesized with low-load Pd supported on resorcinol–formaldehyde resin carbon spheres (CFR) for selective hydrodeoxygenation of vanillin under mild conditions. The as-prepared Pd/CFR-800 catalyst shows excellent activity (>99.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 52 publications
(91 reference statements)
5
51
0
Order By: Relevance
“…19 (c) The HDO of phenol to cyclohexane in a water/n-dodecane biphasic system. 20 National-Local Joint Engineering Laboratory for Energy Conservation in Chemical Process Integration and Resources Utilization, Tianjin Key Laboratory of Chemical Process Safety, School of Chemical Engineering and Technology, Hebei University of Technology, 8 Guangrong Road, Tianjin 300130, China. E-mail: hglh@hebut.edu.cn; Tel: +86 13662190810 MPa) at moderate temperatures (300-400 °C) over heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 (c) The HDO of phenol to cyclohexane in a water/n-dodecane biphasic system. 20 National-Local Joint Engineering Laboratory for Energy Conservation in Chemical Process Integration and Resources Utilization, Tianjin Key Laboratory of Chemical Process Safety, School of Chemical Engineering and Technology, Hebei University of Technology, 8 Guangrong Road, Tianjin 300130, China. E-mail: hglh@hebut.edu.cn; Tel: +86 13662190810 MPa) at moderate temperatures (300-400 °C) over heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In the HDO process, the C-O bonds in the oxygenated compounds are broken and oxygen-containing groups are eliminated by hydrogenation and/or dehydration of CvC and CvO bonds, resulting in reduction of the oxygen content in the final products. 19,[20][21][22][23][24] In order to achieve efficient catalytic HDO, a series of robust reaction systems, involving catalysts and solvents, have been researched and developed. Recently, Schmitt et al 25 developed a Ni/SiO 2 catalyst for hardwood-derived bio-oil selective HDO, achieving more than 50% of the oxygen content removal with low coking and gas formation.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic hydrodeoxygenation (HDO), which can apparently de crease the oxygen content in the reactant, has been reported for the upgrade of biofuels. 9–13 For instance, vanillin (4-hydroxy-3-methoxybenzaldehyde) is a typical component derived from the lignin fraction and one of the only molecular phenolic compounds manufactured on an industrial scale from biomass. 14 It could be hydrodeoxygenated to a potential biofuel, 2-methoxy-4-methylphenol (MMP).…”
Section: Introductionmentioning
confidence: 99%
“…As a typical platform molecule of lignin derivatives, vanillin (VAN) can be used as the reactant for the production of 2-methoxy-4-methylphenol (MMP) which is widely used as an active intermediate for the synthesis of high value-added drugs and fragrances, and many catalytic systems have been developed for the effective production of MMP from VAN. [19][20][21][22][23][24][25][26][27][28][29][30] For example, Xiao's group adapted a self-assembly method to prepare a mesoporous sulfonated melamine-formaldehyde resin (MSMF) supported Pd NPs as an effective catalyst for HDO of VAN and >99% of MMP selectivity with >99% of VAN conversion was achieved after reaction at 110 °C for 2 h over 4.5 wt% Pd/MSMF. 19 Wang et al reported that Pd nanoparticles (NPs) supported on pre-treated CNTs by concentrated HNO 3 efficiently catalyzed VAN to MMP and >98% of MMP selectivity with >99% of VAN conversion was obtained after reaction at room temperature (R.T.) for 1 h over 5.0 wt% Pd/ o-CNT.…”
Section: Introductionmentioning
confidence: 99%